The Effect of Altruism, Moral Obligation on Purchase Intention through e-WOM, on Halal Skincare Products - Paramesti, Nareswari; Kurniawati, Kurniawati (Jurnal Multidisiplin Indonesia, 2024)
The development of marketing communication through technology and the internet has progressed, triggered by technology and the availability of various marketing communication tools. Digital marketing expands the reach of marketing communications, increasing effectiveness with segmentation and personalization for a larger audience. The type of research used in this study is a hypothesis test because there are several hypotheses that will be proposed and tested. The hypothesis testing in this study is a causal hypothesis. The first analysis conducted by the researcher was a descriptive statistical analysis. This analysis is to describe or describe data. The descriptive statistics used are mean and standard deviation.